2023
DOI: 10.2147/jir.s397615
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Systemic Immune-Inflammation Index with Outcomes in Acute Coronary Syndrome Patients with Chronic Kidney Disease

Abstract: Background:The systemic immune-inflammation index (SII; neutrophil × platelet/lymphocyte) is a novel marker for immune and inflammatory status and is associated with adverse prognosis in cardiovascular disease. Methods: In total, 744 patients diagnosed with acute coronary syndrome (ACS) and chronic kidney disease (CKD) were included in our study, received standard therapies, and were followed up. Patients were divided into high and low SII groups according to the baseline SII. The primary endpoint was major ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Table 1 presents a comprehensive overview of the detailed characteristics of the studies incorporated in the meta‐analyses 10,20–27 . Among the selected studies, six were conducted in Asia, while three were conducted in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents a comprehensive overview of the detailed characteristics of the studies incorporated in the meta‐analyses 10,20–27 . Among the selected studies, six were conducted in Asia, while three were conducted in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…A cohort study was conducted by Halpern et al in one center. Regarding prognosis, prospective cohort research by Shi [ 31 ] et al showed that in CKD patients with ACS, higher SII was linked to poor cardiovascular outcomes. In a similar vein, Xie et al [ 41 ] discovered a favorable correlation between SII and abdominal aortic calcification, a frequent CKD consequence.…”
Section: Discussionmentioning
confidence: 99%
“…This study additionally included covariates in the analysis to account for the possible impact of other variables on bone metabolism. Age, race, body mass index (BMI), smoking, hypertension, diabetes mellitus, blood alkaline phosphatase, serum uric acid, blood calcium, blood phosphorus, blood vitamin D, and blood triglycerides were eventually added as covariates based on other research [ 31 , 32 ]. In this instance, the final blood pressure reading was calculated as the average of the body measures, and hypertension was defined as a mean systolic blood pressure of greater than 140 mmHg and/or a mean diastolic blood pressure of greater than 90 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“… 12 , 21 SII has also been described as a predictor of poor clinical prognosis in ACS patients with chronic kidney disease. 22 During a 10-year follow-up study, SIRI was associated with incident CAD and an increased risk of all-cause death and stroke but not MI. 23 Similarly, higher SIRI was associated with more severe disease status in patients with ACS undergoing PCI, and the predictive value was synergistically increased when combined with the GRACE risk score.…”
Section: Introductionmentioning
confidence: 99%